2015
DOI: 10.1152/jn.00302.2015
|View full text |Cite
|
Sign up to set email alerts
|

Split-belt walking adaptation recalibrates sensorimotor estimates of leg speed but not position or force

Abstract: Motor learning during reaching not only recalibrates movement but can also lead to small but consistent changes in the sense of arm position. Studies have suggested that this sensory effect may be the result of recalibration of a forward model that associates motor commands with their sensory consequences. Here we investigated whether similar perceptual changes occur in the lower limbs after learning a new walking pattern on a split-belt treadmill--a task that critically involves proprioception. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 33 publications
14
69
0
Order By: Relevance
“…Changes in step length symmetry were consistent with previous studies (Reisman et al 2005; Malone, Bastian, 2010; Vazquez et al, 2015). Both controls and amputees initially responded to split-belt walking by taking longer steps with the slow leg leading, but returned to baseline step length symmetry by late adaptation.…”
Section: Discussionsupporting
confidence: 92%
“…Changes in step length symmetry were consistent with previous studies (Reisman et al 2005; Malone, Bastian, 2010; Vazquez et al, 2015). Both controls and amputees initially responded to split-belt walking by taking longer steps with the slow leg leading, but returned to baseline step length symmetry by late adaptation.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that the perception of limb position is altered following motor adaptation in locomotion, which supports prior findings that the perception of limb position is susceptible to motor adaptation (e.g., 5,6,15,714 ). However, we only observed perceptual after-effects when subjects actively generated motor commands and not when their legs were passively moved, which is consistent with prior work indicating that afferent signals encoding position remain intact following split-belt walking 16 . These findings contrast multiple reports of shifts in the estimation of hand position following motor adaptation when the arms are moved by the experimenter (e.g., 5–12 ).…”
Section: Discussionsupporting
confidence: 90%
“…We believe that this discrepancy between reaching and locomotion suggests that sensory changes post-adaptation arise from mismatched position estimates from different sensory sources (i.e., proprioception and vision), which is less prominent in walking. We also found that active perceptual effects were not observed in the leading leg’s position, as previously reported 16 , but they were clearly observed in the trailing leg’s position, which had not been assessed before. We posit two potential explanations for the altered estimation of the trailing leg’s position.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Unlike adaptation, energy optimization has not been shown to be cerebellum-dependent [25] or driven by prediction error, but instead results in a remapping between a movement pattern and its expected energetic consequences. It is unclear whether this remapping changes perception (as has been observed in split-belt walking [26,27]) or generalizes to other contexts.…”
Section: Discussionmentioning
confidence: 99%